Robert S. Schwartz, MD, a transformative figure in immunosuppression that revolutionized transplantation - Li, Xian C. (Frontiers in Transplantation, 2023)
While the transplant community celebrated more than a million transplant patients in the United States, we are reminded that our journey to such a celebratory success is the results of remarkable breakthroughs and brilliant innovators. Among those, immunosuppression drugs are undoubtedly a cornerstone of transplant success, an area where Dr. Robert Schwartz is undeniably a transformative figure and a pioneer. His seminal studies on 6-mercaptopurine in 1959 gave birth to an entirely new specialty of immunosuppression that dramatically accelerated the advancement of clinical organ transplantation.